Control interno administrativo y su incidencia en la organización de la Industria arrocera Coronel. cantón El Empalme. año 2014 - Jácome Palacios, Aracely Alexandra (2016)
When carrying out the analysis of the structure and diagnosis of the rice company, you could verify the existence of an organizational structure defined in function of the most important areas that possesses the company. As part of the results the levels of efficiency, effectiveness and effectiveness of the process of inventory of the company were obtained, the same ones that demonstrated that the company fulfills 85, 00% of efficiency, taking like reference the total of the issued reports; also, in relation to the machineries that were acquired during the year 2014 for the process, the result was of 53, 85%, finally 99, 82% of effectiveness was obtained, in function of the realized sales during the year 2014. The evaluation of the system of administrative Internal check that maintains the company for the inventory handling, was carried out in function of the internal check pattern COSO II, the same one that contains 8 components as they are: Set of Control, Establishment of Objectives, Identification of Events, Evaluation of Risks, Answer to the Risk, Activities of Control, Information and Communication and Monitoring, what allowed to identify two discoveries related with the risks to those that he/she faces the company. The financial information that presents the Industry Rice Colonel, allows him to fulfill in a specific way the tributary administration, the same one that is confronted with the respective forms of declaration of the income tax. The internal check report contains the respective discoveries, with its recommendations what will allow him to guide the best decisions in the directives of the company. Keywords: Control, administration, organization, industry